Between Revelation and Constitution: The Sovereignty Fiqh of Muhammad Yamin’s Sociopolitical Ijtihād - Said, Muhtar; Fadli, Moh.; Widiarto, Aan Eko; Al-Uyun, Dhia (Journal of Islamic Law, 2025)
The crucial aspect of studying Indonesian constitutional law that is often overlooked is the dialectic between revelation (religion) and the constitution (state). This interplay significantly influences the foundational thinking of the nation’s architects and shapes constitutional law, as well as critical perspectives on colonialism. This study aims to examine the political-legal thought of Muhammad Yamin by revealing how the interaction between revelation and constitution shaped his ideas regarding the basis and sovereignty of the Indonesian state. Utilizing a textual analysis of historical documents, this research situates Yamin’s thought within the broader context of constitutional formulation as part of an intellectual resistance against colonial hegemony. The findings reveal that Yamin’s concept of sovereignty fiqh (Islamic jurisprudence), which is grounded in the Islamic principle of shūrā (deliberation), represents a sociopolitical ijtihād (independent reasoning) that systematically critiques the Netherlands-Indonesia Union. Furthermore, it clearly articulates his idea of a “pembanding” or comparator, a conceptual precursor to judicial review. Theoretically, this study expands the scope of sociopolitical fiqh within contemporary constitutional discourse. [Aspek krusial dalam kajian hukum ketatanegaraan Indonesia yang sering diabaikan adalah dialektika antara wahyu (agama) dan konstitusi (negara). Interaksi ini memiliki pengaruh yang signifikan terhadap dasar pemikiran para perumus bangsa dalam membentuk hukum konstitusi, serta memberikan perspektif kritis terhadap kolonialisme. Penelitian ini bertujuan untuk mengkaji pemikiran politik-hukum Muhammad Yamin dengan mengungkap bagaimana interaksi antara wahyu dan konstitusi mengonstruksi gagasannya mengenai dasar dan kedaulatan negara Indonesia. Melalui analisis tekstual terhadap dokumen-dokumen historis, penelitian ini menempatkan pemikiran Yamin dalam konteks yang lebih luas dari proses perumusan konstitusi sebagai bagian dari perlawanan intelektual terhadap hegemoni kolonial. Temuan ini mengungkap bahwa konsep fikih kedaulatan Yamin, yang berakar pada prinsip syūrā dalam Islam, merupakan suatu ijtihad sosio-politik yang secara sistematis mengkritik Uni Indonesia-Belanda. Selain itu, konsep tersebut secara jelas mengartikulasikan gagasannya tentang “pembanding”, yang merupakan cikal bakal konseptual dari uji materiil (judicial review). Secara teoretis, studi ini memperluas cakupan fikih sosio-politik dalam wacana ketatanegaraan kontemporer.]